Food Prices, Access to Markets and Child Undernutrition in Ethiopia - Brenton, Paul; Nyawo, Mike (World Bank, Washington, DC, 2019)
This paper looks at how changing food prices affect child undernutrition in Ethiopia. It derives height for age (stunting) and weight for height (wasting) as indicators of child undernutrition from the two most recent years of the Livings Standards Measurement Survey and utilizes market prices for key cereals, teff, wheat, and maize at the zone level across all regions of the country. Using a panel data fixed effects model, the analysis finds that, contrary to previous studies, rising crop prices are positively associated with improved child stunting rates for children between ages 6 months and 5 years, while the results for wasting are not conclusive. These results suggest that across the board policy interventions that seek to suppress cereal price increases may have adverse effects on poverty reduction in the long term by undermining potentially positive impacts on child nutrition.